Trends in known and undiagnosed diabetes, HbA1c levels, cardiometabolic risk factors and diabetes treatment target achievement in repeated cross-sectional surveys: The population-based Tromsø Study 1994-2016 - Langholz, Petja Lyn; Wilsgaard, Tom; Njølstad, Inger; Jorde, Rolf; Hopstock, Laila Arnesdatter (BMJ Open, 2021)
Objectives - The aim of this study was to investigate time trends in known and undiagnosed diabetes, glycated haemoglobin (HbA1c) levels and other cardiometabolic risk factors in the general population as well as treatment target achievement among those with diabetes. Design and setting - Repeated cross-sectional surveys in the population-based Tromsø Study. Methods - We used age-adjusted generalised estimating equation models to study trends in self-reported and undiagnosed (HbA1c ≥6.5%) diabetes, cardiometabolic risk factors and the metabolic syndrome in 27 281 women and men aged 40–84 years examined in up to four surveys of the Tromsø Study between 1994 and 2016. Further, we analysed trends in diabetes treatment target achievement. Results - During 1994–2016, diabetes prevalence increased in women (2.3% to 4.6%) and men (2.4% to 5.8%) and in all age groups, while the proportion of undiagnosed diabetes in women (32% to 17%) and men (37% to 24%) decreased. Blood pressure and total cholesterol decreased, while waist circumference increased in participants with and without diabetes, leading to a relatively stable prevalence of the metabolic syndrome throughout the study period. There was a marginal increase in HbA1c levels among participants without diabetes. Only half of those with diabetes achieved the treatment target of HbA1c ≤7.0%. Conclusion - In the last two decades, diabetes prevalence increased, while the proportion of undiagnosed diabetes declined. The prevalence of the metabolic syndrome remained stable throughout, driven by opposing trends with an increase in obesity and a decrease in other cardiometabolic risk factors. HbA1c treatment target achievement did not improve.